Importance of malnutrition in patients with cirrhosis - Göktürk, Hüseyin Savaş; Selçuk, Haldun (Turkish Journal of Gastroenterology, 2015)
Abstract Malnutrition is common in patients with chronic liver disease and is associated with poor outcomes. Inadequate intake, poor quality diet, maldigestion, malabsorption, altered macronutrient metabolism, and hypermetabolism all contribute to the development of malnutrition in this patient population. Although it is generally easy to detect, clinicians often overlook malnutrition and its measurement is complicated by the lack of a simple, standardized diagnostic method. Early detection of malnutrition and multidisciplinary treatment approaches greatly increase the probability for successful outcomes.